Constructing the Meaning of Party Ideology for Women Politicians of the Prosperous Justice Party (PKS) - Evie Ariadne Shinta Dewi; Vera Wijayanti Sutjipto; Suwandi Sumartias; Hanny Hafiar (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
The meaning of ideology within a political party is related to the way politicians understand their party's ideology. Therefore, all politicians, including female politicians, have their own meaning construction according to their understanding. This study aims to find out the meaning of party ideology constructed by PKS female politicians. Constructivism is the paradigm used in this research with phenomenological methods. The sources of this research are 14 PKS female politicians who are currently legislative members at the national, provincial, city or district level for the service period 2019 to 2024. The results of this study indicate that there are two meanings of political party ideology built by PKS women politicians, namely religious meaning and humanistic meaning. The first meaning is the religious meaning, which consists of adhering to Ahl al-Sunnah wa al-Jama'a and Bayan and Da'wah Tarbiyah. The second meaning is the humanistic meaning, which is having good morals, making political life a part of everyday life, showing justice and welfare, having a sense of happiness, as well as walidatul umat and strengthening the Ummah.